A STUDY OF ULTRASONIC ABSORPTION OF SOME AMINO ACIDS AND THEIR MIXTURES AT PHYSIOLOGICAL pH (Journal of Sciences, Islamic Republic of Iran)
In this paper, the ultrasonic absorption of amino acids was measured using a small cylindrical resonator at physiological pH and 25°C and a concentration of 0.1. M. The absorption of mixtures of some amino acids was also measured. In the case of cysteine-histidine, the absorption of mixtures is much larger (more than twice) than the summation of absorption of the individual amino acid. This may be due to the weak bonds between the side chain of histidine and the SH group of cysteine molecules. As for the absorption of proteins, it could also be due to weak bonds mentioned earlier